New Headway : Intermediate Workbook Without Key - Soars, John and Soars, Liz (Oxford, New York Oxford University Press, 2003)
The third edition of the best-selling course, maintaining the successful core content but updated and refreshed.
Include Color Illustration
Keywords: English language -- English language--Pronunciation -- English language--Study and teaching--Foreign speakers